Pengembangan model bimbingan kelompok berbasis islami untuk meningkatkan kecerdasan sosial siswa SMK - Riki Maulana (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The research is aimed to 1) know the implementation of group counseling in private vocational school in Semarang. 2) know the social intelligence condition in SMK Roudiotus Saidiyyah Semarang. 3) Produce Islamic teaching based group counseling model to increase social intelligence of students in Roudiotus Saidiyyah Semarang. 4) ehther or not the implementation of the islamic teaching based group counseling model effectiveness in increasing social intelligence of the students in Roudiotus Saidiyyah Semarang. The research method used is Research and Development (R & D) method. The data analysis technique used are both qualitative and quantitative. The findings were the Islamic teaching based group counseling model consists of rasional, vision and misson, objectives, the model content, the stages in Islamic teaching based group counseling model, role and function of the group leader, group member qualification, evaluation and follow up.